(3GdfXQjI GdGbJUGOjI GdcdjI (B:s (3eMGVQGJ hJeGQjf (B/s - (3RQbhf, eMeOs; (3QMeGf, CeGds ((3GdLRGFQ(B: s (3OjhGf GdeWHhYGJ GdLGeYjI(B, s, 2017)
(3dbO LGAJ gPg GdeWHhYI GdJOQjSjI GdeYfhfI H` (B: (3GdfXQjI GdGbJUGOjI GdcdjI(B: (3eMGVQGJ hJeGQjf, dJZWj ehGVjY GdJMdjd GdGbJUGOj Gdcdj Ydi CSGS fXQj hJWHjbj, hgj ehLgI CSGSG Gdi WdHI GdSfI GdKGfjI Ydhei GbJUGOjI, Ydhe JLGQjI hYdhe GdJSjjQ aj GdWhQ GdChd ef fXGe d(B.(3e(B.(3O debjGS GdEbJUGO Gdcdj GdeGdj hGdEbJUGO Gdcdj GdeYeb, MjK CfgG JgOa Gdi eSGYOI WdHI GdLGeYGJ hGdeYGgO Hage Cge ehGVjY GdfXQjI GdGbJUGOjI GdcdjI hGdeMOOI aj GdebQQGJ , hbO MGhdJ GdcGJHI YQV Cge YfGUQ gOg GdeWdhYI HCSdhH Ydej eHSW hhGVM, hbO Je JOYjegG HeLehYI ef GdJeGQjf GdeMdhdI aj fgGjI cd aUd(B. s
(3eQGLY U(B.269 (3bGFeI GdLOGhd U(B.275 (3bGFeI GdCTcGd U(B.277 (3bGFeI GdGNJUGQ hGdQehR U(B.281s
Keywords: (3GdEbJUGO Gdcdjs